Social-emotional learning profile of junior high school students in Java - Astuti, Budi; Purwanta, Edi; Lidyasari, Aprilia Tina; Bhakti, Caraka Putra; Lestari, Rizqi; Amedome, Sedem Nunyuia (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
Social-emotional learning is an essential aspect of an individual's development. Thisresearch aims to determine the profile of social-emotional learning and differences in social-emotional learning scores based on gender and grade level among junior high school students in Java. This research uses a quantitative approach with a comparative research type. The sample in this study was 2036 junior high school students on the island of Java. The data collection technique in this research used a social-emotional learning scale, which was tested for validity and reliability using the RASCH model. Data analysis techniques were carried out using descriptive statistics and the ANOVA test. The results show that the majority of junior high school students in Java had a high score in social-emotional learning (N=65.4%), and only 0.1% of students categorized indeficient. Students' social-emotional levels were not influenced by gender or grade level. The self-management aspect had the lowest score, and the self-awareness aspect had the highest score in social-emotional learning. It is hoped that the results of this research can provide an overview of the conditions of social-emotional learning in students and become a reference for the development of social-emotional learning program in schools.Guidance and Counseling teachers can improve the lowest aspect of social-emotional learning through various techniques and methods so students can have good social-emotional learning skills in all aspects. Future research needs to explore the factors that influence high levels of SEL in students and expand the research sample to obtain broader generalizations.